Consideration of Mithliy and QÄ«miy in Debt Service under the Islamic Law of Contract - AbdulWahab Muhammad Jamiu Elesin; Liman Saâ€˜adatu Hassan (Universitas Muhammadiyah Yogyakarta, 2022)
In order to satisfactorily discharge a financial obligation, Islamic finance prescribes similar for similar or equal for equal (mithliy bi mithliy), unless where similar becomes impossible or unobtainable, then the resort is made to worth or value (qÄ«mah). However, opinions of the jurists differ as to determination, identification or verification precisely of what is mithliy, which may affect the actualisation of debt settlement and make it ambiguous. In this situation, the substitution of qÄ«miy for mithliy becomes inevitable. In doing so, fear of falling into riba or causing injury to either debtor or creditor arises, particularly where rebatable (usurious) items such as gold and silver (dhahb wa fiá¸á¸ah), currencies (nuqÅ«d), animal (á¸¥ayawÄn) are involved. This paper, therefore, studied scholarly opinions about the identification of â€œsimilar itemsâ€ (mithliyÄt) and â€œvalued itemsâ€ (muqawwamÄt). It used primary and secondary sources of SharÄ«Ê»ah. Fiqh manuals, books of tafsÄ«r, á¸¥adÄ«th and relevant periodicals and articles were consulted. The study revealed that parties face difficulties in actualising similarity while settling financial obligations. Therefore, the paper suggested the inclusion of a â€œstatement of similar or worth propertyâ€ while making a financial agreement.